Transcriptional Regulation of β-Defensin Gene Expression in Tracheal Epithelial Cells - Diamond, Gill (American Society for Microbiology, 2000)
Innate immunity provides an ever-present or rapidly inducible initial defense against microbial infection. Among the effector molecules of this defense in many species are broad-spectrum antimicrobial peptides. Tracheal antimicrobial peptide (TAP) was the first discovered member of the β-defensin family of mammalian antimicrobial peptides. TAP is expressed in the ciliated epithelium of the bovine trachea, and its mRNA levels are dramatically increased upon stimulation with bacteria or bacterial lipopolysaccharide (LPS). We report here that this induction by LPS is regulated at the level of transcription. Furthermore, the transfection of reporter gene constructs into tracheal epithelial cells indicates that DNA sequences in the 5′ flanking region of the TAP gene, within 324 nucleotides of the transcription start site, are responsible in part for mediating gene induction. This region includes consensus binding sites for NF-κB and nuclear factor interleukin-6 (NF IL-6) transcription factors. Gel mobility shift assays indicate that LPS induces NF-κB binding activity in the nuclei of these cells, while NF IL-6 binding activity is constitutively present. The gene encoding human β-defensin 2, a human homologue of TAP with similar inducible expression patterns in the airway, was cloned and found to have conserved NF-κB and NF IL-6 consensus binding sites in its 5′ flanking region. Previous studies of antimicrobial peptides from insects indicated that their induction by infectious microbes and microbial products also occurs via activation of NF-κB-like and NF IL-6-like transcription factors. Together, these observations indicate that a strategy for the induction of peptide-based antimicrobial innate immunity is conserved among evolutionarily diverse organisms.